Effectiveness of skin to skin contact between mother and healthy newborn in reducing pain due to intramuscular injection - H.Khodam (M.Sc); T.Ziaee (M.Sc); S.A.Hosseini (M.Sc) (مجله دانشگاه علوم پزشکی گرگان, 2002)
Compared with older children and adults, neonates are more sensitive to pain and more vulnerable to long-term effects. Despite the clinical importance of neonatal pain, current medical practices continue to expose infants to repetitive, acute, or prolonged pains. This specific intervention are necessary for reduced the neonatal pain experiences. This is an experimental study of determine the effectiveness of skin contact between mother and her healthy full-term newborn to reduce pain experience by the infant during intramuscular injection. The sample population was 30 healthy full-term newborns delivered at university hospital in Gorgan. The samples and controls were chosen randomly. During intramuscular injection case group was being helped by their mothers under cloth that directly were contact with their abdominal and chest skin and newborn in control group swaddled in crib on the bed before, after and during injection. Behavioral responses (Facial changes, crying, …) and physiologic responses (Heart rate and O2 saturation of arterial blood) of newborns were noted before, after and during intramuscular injection. The results show that there was no significant difference in behavioral and physiologic responses caused by pain between two groups, except crying time (38.2 second in control group and 35.5 second in case group). Finding from this study indicate that skin-to-skin contact has a clinically important effect on the pain of intramuscular injection, if we can prepare physically and emotionally a good situation.